Taxonomic revision of Chironius flavolineatus (Jan, 1863) with description of a new species (Serpentes: Colubridae) - Hamdan, Breno; Fernandes, Daniel S. (Zootaxa, 2015)
We conducted a taxonomic review of Chironius flavolineatus on the basis of continuous and discrete morphological characters. We recognize a new species which is distinguished from all currently recognized congeners by the following unique combination of characters: first third of body black or dark gray; vertebral stripe yellowish or creamish white distinct from dorsals of nape and extending throughout almost whole body length; head dorsum tan to brown, distinct from background color of first third of body; posterior temporal scales ranging one to four; cloacal shield frequently divided; two to four rows of keeled dorsal scales at midbody; venter ground color gradually darkening towards cloaca; region of medial constriction of hemipenis slightly covered with spinules separating calyces of apex from spines below region of constriction; in lateral view, sulcus spermaticus positioned on convex face of hemipenis; ascending process of premaxilla oblique anteroposteriorly to longitudinal axis of skull; optic fenestrae not exceeding frontoparietal suture; posterior border of supratemporal exceeding braincase; dorsoventral axis of quadrate oblique mesolaterally, moving away from longitudinal axis of skull. Furthermore, we provide data on morphological variation, distribution, and an emended diagnosis for C. flavolineatus.